Kenya Airways: A case study of privatization - Oyieke, Samuel O. (The African Economic Research Consortium, 2002)
Various commissions and Kenya’s Comptroller and Auditor General consistently point to the inefficiency and mismanagement of parastatals (state-owned enterprises). Consequently, their advice has been to divest and privatize. The main reasons advanced by the Kenyan government for embracing privatization were to reduce the fiscal burden, develop the private sector, broaden ownership of wealth and raise revenue for the cash-strapped government. As these goals are mutually exclusive, achieving them, especially in a poor country like Kenya, is problematic. This has made privatization a rather unpopular process in the country. Presenting a case for privatization requires documentary evidence of successful privatization. It is in this respect that Kenya Airways was selected as a case study. The findings of the study demonstrate clearly that successful privatization is possible. The study concludes that privatization can achieve its objectives if conducted systematically and transparently. The support of the general public is possible in an atmosphere free of suspicion and with a free flow of information before and after privatization.